The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.22621/cfn.v128i2.1582
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of baling twine in the landscape near Osprey (<em>Pandion haliaetus</em>) nests: implications for nestling entanglement

Abstract: Seacor, Renee, Kayhan Ostovar, and Marco Restani. 2014. Distribution and abundance of baling twine in the landscape near Osprey (Pandion haliaetus) nests: implications for nestling entanglement. canadian Field-Naturalist 128(2): 173-178.Polypropylene baling twine used by Ospreys (Pandion haliaetus) during nest construction creates a risk of entanglement for nestlings and adults on the yellowstone River, Montana. In 2013, we evaluated the abundance of twine in 2-km-radius buffer zones centred on 38 nests for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Filaments of plastics (thread, rope, fishing line, string) were frequently recorded in some nests, such as numbers 1, 3, and 7 (A and B groups; Table 1). These elements are particularly prone to cause entanglement of birds inside the nest and have been shown to lead to injuries or mortality in other species (Seacor et al 2014;Votier et al 2011). Although none of the nests studied here contained entangled fledglings, we suppose that the same risk exists for birds in freshwater (Blettler et al 2019) or terrestrial environments.…”
Section: Potential Risks Given By the Recorded Plastic Typesmentioning
confidence: 74%
See 1 more Smart Citation
“…Filaments of plastics (thread, rope, fishing line, string) were frequently recorded in some nests, such as numbers 1, 3, and 7 (A and B groups; Table 1). These elements are particularly prone to cause entanglement of birds inside the nest and have been shown to lead to injuries or mortality in other species (Seacor et al 2014;Votier et al 2011). Although none of the nests studied here contained entangled fledglings, we suppose that the same risk exists for birds in freshwater (Blettler et al 2019) or terrestrial environments.…”
Section: Potential Risks Given By the Recorded Plastic Typesmentioning
confidence: 74%
“…On the other hand, the use of plastic materials has evident negative consequences such as entanglement inside the nest, as well as the yet little-known reduction in bird fitness (Seacor et al 2014). How potential benefits balance the entanglement, ingestion, and toxin hazards of plastic nest materials is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic string, fishing nets, and angling gear are resistant materials occurring in the sea (far from nest sites) as well in the nest (collected by adults). These items often cause entanglement, leading to mortality or injuries (Baker et al 2002 ; Seacor et al 2014 ). Entanglement has been recorded in 25% of 312 studied seabird species (Gall and Thompson 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…plastic strings, foil) is collected from agricultural lands as nesting material and incorporated into nests (Tryjanowski et al 2006 ). Plastic string is one of the most common anthropogenic materials used by terrestrial species as nesting material (Antczak et al 2010 ; Seacor et al 2014 ). This material has been commonly used in Polish agriculture since 1982 for tying, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…I had banded the brood of three nestlings on 15 July 2014 and returned to the site because volunteer nest monitors were concerned that one of the nestlings had become entangled in baling twine. Twine entangled an estimated 3.3% of Osprey nestlings within the Yellowstone River watershed in 2012-2013 (Seacor et al 2014), so their concern was warranted. The monitors reported that two of the three nestlings had fledged and that the remaining offspring had material hanging from its feet that appeared to hinder flight.…”
mentioning
confidence: 99%